Specific ludic learning tasks in EFL oral expression development: A dialogical approach. - López Aguilar, Armando Maximiliano (Facultad de Filosofía y Letras, 2018)
Current language learners are in search of a different approach in which their twenty-first-century skills are developed properly to not only understand their language learning process, but complement, internalize, and blend it with personal thoughts on the way to express a meaning related to them. The purpose of this investigation is to consider the influence of ludic learning tasks presented in EFL third-graders when learning a foreign language through a dialogical teaching approach. This investigation is framed into the action research paradigm to reflect and solve the low language understanding presented in the population that participated in it. This research is based on the principal authors of ludic task concept as an interactive activity (Arias & Castiblanco, 2015; Castañeda, 2010; Molina, 2015; and Ortega, 2012) and dialogical approach applied in the classroom (Callander, 2013; Fernández, 2014; and Wells, 1999), among others. The analysis of this investigation required of an elementary English as a Foreign Language group consisted of 35 students in which a written language evaluation, a survey based on ludic learning tasks, and an oral language rubric were as data gathering instruments. All this is to observe actual language knowledge in students in order to present a didactic sequence planning to improve learning and oral communicative expression in EFL third-grade learners.